Manajemen Jalan Nafas dengan Kombinasi Chest Physiotherapy dan Terapi Oksienasi pada Pasien Pneumonia - Nur Afika Syam; Haeril Amir; Fitria Fitria (Wal'afiat Hospital Journal, 2025)
Pneumonia is a lower respiratory tract infection that may cause secretion retention, crackles, tachypnea, and reduced oxygenation, requiring measurable airway clearance and oxygen support in the emergency department. This case report describes clinical improvement in a single case following a combination of Chest Physiotherapy (CPT) and oxygen therapy. The patient presented with dyspnea, productive cough, and fever. Baseline assessment showed crackles, thick sputum difficult to expectorate, RR 27–28 breaths/min, SpO₂ 93%, temperature 38°C, and chest X-ray infiltrates consistent with pneumonia. The primary nursing diagnosis supported ineffective airway clearance with the need for oxygenation support. Interventions included structured CPT (postural drainage, percussion/vibration, deep-breathing, and effective coughing) and oxygen via nasal cannula titrated to target saturation. Outcomes were assessed quantitatively at T0 (baseline), T1 (after one session, ~1–2 h), and T2 (~24 h): RR, SpO₂, lung sounds, sputum characteristics, dyspnea (Borg 0–10), accessory muscle use, and temperature. Gradual clinical improvement was observed (RR 27–28 to 22 breaths/min; SpO₂ 93% to 96%), with reduced crackles, easier sputum expectoration, decreased dyspnea, and lower temperature. Generalization is limited due to the single-case design and concurrent medical therapies.